The Application of Biotechnology in the Diagnosis of Diseases of Public Health Importance in Mexico - Martínez-González, Sonia -Mirén (2021)
Although the diagnostic techniques of medical biotechnology are being applied in Mexico, there is still a significant percentage of people who do not have access to health services, a result of the country's economic inequality. This article aims to present the impact in Mexico of several diseases (COVID-19, acute diarrheal disease, cervical cancer, breast cancer, leishmaniasis, acute kidney injury and neurocysticercosis), the strategies implemented in their diagnosis and control, as well as perspectives of novel diagnostic tests. The article was conducted through a review of online documents from the Mexican government and scientific articles that study the implementation and characteristics of biotechnological tools for disease diagnosis. In the case of COVID-19, the availability of accurate and rapid procedures for its diagnosis has proven to be of vital importance in the control of this disease, as well as in the understanding of infection and immunity processes. In the case of acute diarrheal disease resulting from rotavirus infection, the high morbidity and mortality of diseases cannot be completely controlled until the quality of life of the population is improved. The tools of biotechnology in diagnostics applied through public programs to vulnerable populations provide a way to close the health gap between developed and developing areas. Even so, it must be considered that the amount of resources they use is still high.